Refugee protection in international law : (Cambridge University Press, 2003)
Millions of people are forced today to flee persecution. The core international legal instrument on which they must rely to find safety is the 1951 Convention Relating to the Status of Refugees. This book examines key challenges the Convention faces, on the basis of nine papers by eminent international refugee lawyers, which were then discussed at an expert roundtable meeting in 2001 as part of UNHCR's Global Consultations on International Protection.